2015
DOI: 10.1016/j.jjcc.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of warfarin for stroke prophylaxis in patients with atrial fibrillation or atrial flutter in Korea

Abstract: A high portion of AF/AFL patients with CHADS2 score ≥2 were undertreated with warfarin. As ischemic stroke is one of the leading causes of death in Korea, a more aggressive approach to prevent stroke in patients with AF/AFL is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
4
23
1
Order By: Relevance
“…female gender, vascular disease, and prior ICH, were associated with non-use of OAC therapy in the NOAC era. Previous studies have reported on the underuse of OAC therapy in female patients with AF in accordance with our results [ 3 , 5 , 13 , 25 ]. The reason of OAC underuse in females was not fully understood, but in the VKA era, female gender was a risk factor for poorer anticoagulation control as assessed by time in the therapeutic range of the INR [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…female gender, vascular disease, and prior ICH, were associated with non-use of OAC therapy in the NOAC era. Previous studies have reported on the underuse of OAC therapy in female patients with AF in accordance with our results [ 3 , 5 , 13 , 25 ]. The reason of OAC underuse in females was not fully understood, but in the VKA era, female gender was a risk factor for poorer anticoagulation control as assessed by time in the therapeutic range of the INR [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Few reports on OAC use for stroke prevention are available for the Korean AF population. Lee et al reported OAC underuse in patients with AF and CHADS 2 score ≥ 2 and ATRIA bleeding risk score ≤ 4 using the National Patients Sample database of 2009 (n = 8,475) [ 5 ]. OAC use and antithrombotic therapy, including OAC and aspirin use, were estimated at 36.0% and 79.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are clear benefits of OAC therapy for stroke prevention in high-risk AF patients, OAC is still underused in many patients with AF, particularly in the warfarin era. 12,[45][46][47] The narrow therapeutic range, needs of frequent monitoring/dose adjustments, and interactions with food or drug have made physicians and patients reluctant to use warfarin. 45 The landscape of stroke prevention in AF patients changed with the availability of NOACs.…”
Section: Ischemicmentioning
confidence: 99%
“… 27) Although recent guidelines recommend the use of OAC therapy in AF patients with a CHA 2 DS 2 -VASc score ≥2, these drugs have been generally underused for stroke prevention. 11) 28) 29) Previous studies performed in a Korean population have reported that female sex, old age, and Medical Aid beneficiaries are common predictors for OAC underutilization. 28) 29) Several reports have discussed the role of SES in determining the choice of antithrombotic therapy for stroke prevention in AF patients.…”
Section: Discussionmentioning
confidence: 99%